A EFETIVAÇÃO DA POLÍTICA DE COTAS COMO ESTRATÉGIA DE ENFRENTAMENTO AO RACISMO: tensões e avanços na atuação da Comissão de Heteroidentificação da UFMA nos anos de 2020 e 2021 - MORAES, Alan Jeffeson Lima de (2022)
This work aims to analyzes the implementation process of the racial quota policy at the Maranhão Federal University, especially the role of the heteroidentification commission in the racial identification process of the recipients of the affirmative action policy for admission to college education. Affirmative actions were identified to combat racism and at the same time implement the equality material principle provided in the constitutional text. Some analytical categories such as racial identification, racism, racial democracy, class, self-declaration and hetero-identification were used to understand the reproduction mechanisms of historically structured power relations rooted in the social imaginary. It was necessary to rescue the implementation process of the racial quota policy in the global context with a focus on the Brazilian reality, which in recent years has experienced a naturalization process and trivialization of the multifaceted forms of racist manifestations, the result of a cruel and enslaving culture, which reproduces sophisticated forms of racial intolerance perpetuation against black people. In this way, discussions about racial identification in the selection of beneficiaries’ process of the quota policy at UFMA triggered tensions in the heteroidentification performance committee that resulted in administrative and judicial proceedings, boosting the racial issues problematization in the educational scope. Furthermore, the debate involving racial issues is confused with discussions about social class, which makes the struggle for the black people right affirmation those are invisible and is reflected not only in the electing process of beneficiaries of the quota policy, but also stresses social and policies. In this sense, considering the need context to review the quota law, this study also sought to explore the various legislative proposals presented at the national congress in order to change the quota policy nuances, sometimes expanding, sometimes restricting its scope, including effective exclusion of blacks, as a criterion for classifying candidates. Thus, there is a necessary inquiry about the maintenance and development perspectives of affirmation policies of rights for the black community, since there is a constant resistance in recognizing the need to combat structural and conjunctural racism.